Is the sonographic degree of blood supply a new prognostic factor? - Sohn, Christof; Thiel, Claudia; Baudendistel, Anja; Kaufmann, Manfred; Bastert, Gunther (The breast, 1996)
The aim of the present study was to investigate the relationship between the biological behaviour of breast cancer and ultrasonographically detected blood flow. The investigations were carried out with a prototype colour ultrasound unit — CSA Acoustic Imaging, Phoenix, MEM colour technique. This machine identifies very low blood flow velocities that are not detected by conventional Doppler methodology. Blood flow was assessed on the visual colour information obtained (class I low, blood flow, single colour pixels - class III, high blood flow, several colour areas). Although the subjectivity of this classification is a disadvantage there was no intra-observer variation in this study. In 119 patients with invasive ductal breast carcinomas, there was a close correlation between the degree of blood flow and tumour size, lymph node status, S-fraction, ploidy and receptor status. Approximately 91% of patients with class I blood flow had negative lymph nodes whereas 81 % of women with class III blood flow had lymph node metastases. Low flow was associated with diploid tumour cells, an S-fraction < 5.0 and positive hormone receptor status. Aneuploid tumour cells, high S-fraction and negative hormone receptor status correlated strongly with high blood flow. This correlation between established prognostic factors and ultrasonographic assessment of blood flow indicates that blood flow in a tumour may have prognostic value and further studies are indicated.
Elektronische Reproduktion der Druck-Ausgabe 12. März 2004
Gesehen am 26.02.2024